2021
DOI: 10.3390/horticulturae7100401
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the 1-Aminocyclopropane-1-carboxylic Acid Synthase (ACS) Genes and Their Possible Role in Sand Pear (Pyrus pyrifolia) Fruit Ripening

Abstract: Ethylene production is negatively associated with storage life in sand pear (Pyrus pyrifoliaNakai), particularly at the time of fruit harvest. 1-Aminocyclopropane-1-carboxylic acid synthase (ACS) is the rate-limiting enzyme in ethylene biosynthesisand is considered to be important for fruit storage life. However, the candidate ACS genes and their roles in sand pear remain unclear. The present study identified 13ACS genes from the sand pear genome.Phylogenetic analysiscategorizedthese ACS genesinto four subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The rate-limiting enzyme in the ethylene biosynthesis process, 1-aminocyclopropane-1-carboxylic acid synthase (ACS), is considered to be crucial for the fruit storage life. Jing-Guo Zhang's [10] study identified 13 ACS genes in the genome of the sand pear. The sand pear genome sequencing data revealed a total of 13 ACS genes, 9 of which were novel members.…”
mentioning
confidence: 99%
“…The rate-limiting enzyme in the ethylene biosynthesis process, 1-aminocyclopropane-1-carboxylic acid synthase (ACS), is considered to be crucial for the fruit storage life. Jing-Guo Zhang's [10] study identified 13 ACS genes in the genome of the sand pear. The sand pear genome sequencing data revealed a total of 13 ACS genes, 9 of which were novel members.…”
mentioning
confidence: 99%